Rat in a Cage: Trappability of Urban Norway Rats (Rattus norvegicus) - Byers, Kaylee A.; Lee, Michael J.; Bidulka, Julie J.; Patrick, David M.; Himsworth, Chelsea G. (Frontiers in Ecology and Evolution, 2019)
Understanding the local ecology of urban Norway rats (Rattus norevgicus) is necessary to inform effective rat mitigation strategies. While Capture-Mark-Recapture (CMR) methods can be used to acquire such ecological information (e.g., abundance, movement patterns, and habitat use), these techniques assume that all individuals of the study population are equally trappable. To test whether urban rats adhere to this assumption, we conducted a four-week CMR study in an urban neighborhood of Vancouver, Canada, to evaluate whether rat characteristics (i.e., age, sex, size, wound status, and infection with the pathogen Leptospira spp.) were associated with trappability. We found that the majority of rats entered traps in the first two weeks of trapping, and that larger rats were caught earlier in the trapping period. However, smaller, sexually immature rats were recaught more often than were larger, sexually mature rats, suggesting that prior capture affects the ability to recapture urban Norway rats. This highlights the need for CMR studies to account for size and sexual maturity when interpreting data.